Implementation of Mobile Library Cars (MPK) to Improve Community Reading Interest in the Provincial Library and Archives Service East Java - Shevila Afriza Saputri; Diana Hertati (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This research discusses the implementation of the Mobile Library Car (MPK) at the East Java Province Library and Archives Service in increasing the public's interestin reading, especially school students. Data was obtained through in-depth interviews, direct observation and the author's experience. The results show that the success of MPK is influenced by a clear organizational structure, effective division of tasks, and also good logistics management. This program runs with participation and support from the government and community. The results of implementation include the impact of the Mobile Library Car (MPK) program on increasing interest in reading, the role of library staff interaction, the use of digital technology, the provision of varied book collections, and maintaining collaboration with related parties. So that the correct implementation of the strategy in the Mobile Library Car Program (MPK) becomes an effective means of building sustainable literacy habits. Keywords: East Java, Interest in reading, iteracy, Mobile Library Car, Program implementation.